2020
DOI: 10.1063/5.0018541
|View full text |Cite
|
Sign up to set email alerts
|

Finger instability of oscillating liquid–liquid interface in radial Hele-Shaw cell

Abstract: The dynamics of the interface between two immiscible liquids with a high viscosity contrast is studied experimentally when the liquids are pumped through a radial Hele-Shaw cell. Two cases are considered: a monotonous radial displacement of the viscous fluid, when the classical Saffman–Taylor instability develops, and an oscillatory interface motion due to harmonic flowrate modulation in the absence of the average displacement flow. At small amplitudes of flowrate modulation, the interface performs axisymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…For example, in CO 2 sequestration in aquifer systems, the CO 2 fingering tends to bypass the brine, leading to the unstable propagation of CO 2 plume and larger contact between CO 2 and rock. To investigate the fundamental mechanisms of VF, a large number of experiments have been conducted in real porous media or a Hele-Shaw cell [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in CO 2 sequestration in aquifer systems, the CO 2 fingering tends to bypass the brine, leading to the unstable propagation of CO 2 plume and larger contact between CO 2 and rock. To investigate the fundamental mechanisms of VF, a large number of experiments have been conducted in real porous media or a Hele-Shaw cell [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…A Hele-Shaw cell constitutes two parallel glass plates separated by a narrow space [1][2][3][4] . The distance between the two glass plates is referred to as the width of the gap of the cell.…”
Section: Vf Viscous Fingering Hs Hele-shawmentioning
confidence: 99%
“…We notice that mainly two kinds of the geometrical con guration of HSC are used in studies, i.e., rectilinear HSC [17,18] and radial HSC [19,20]. These Numerous studies reported that VF instability may be controlled through operating parameters, i.e., ow rate [21,22], viscosity ratio [23,24], surface tension [25,26], and, surface wettability [27,28]. Kozlov et al [21] adopted harmonic ow rate in the radial ow displacement process in HSC.…”
Section: Introductionmentioning
confidence: 99%